Does high-dose perioperative use of statins ameliorate acute kidney injury following cardiac surgery? - van Groenendael, Roger; Pickkers, Peter (Journal of Thoracic Disease, 2016)
Acute kidney injury (AKI) is a well-known, frequent complication in patients after cardiac surgery, occurring in 7% to 40%, depending on its definition (1). Subsequently, it is independently associated with substantial morbidity [such as need for renal replacement therapy, longer length of hospital stay and progression of chronic kidney disease (CKD)] and mortality (2). Even a minimal increase in post-operative serum creatinine is associated with an increased mortality in cardiac surgery patients (3).